The Upstairs Market for Large-Block Transactions: Analysis and Measurement of Price Effects - Keim, Donald B.; Madhavan, Ananth (Review of Financial Studies, 1996)
[This article develops a model of the upstairs market where order size, beliefs, and prices are determined endogenously. We test the model's predictions using unique data for 5,625 equity trades during the period 1985 to 1992 that are known to be upstairs transactions and are identified as either buyer or seller initiated. We find that price movements prior to the trade date are significantly positively related to trade size, consistent with information leakage as the block is "shopped" upstairs. Further, the temporary price impact or liquidity effect is a concave function of order size, which may result from upstairs intermediation.]